Vote-buying Practices in the Kesu Indigenous Communities During the 2020 North Toraja Elections - Zain, Aqidatul Izza; Wardani, Sri Budi Eko (Jurnal Politik Indonesia: Indonesian Political Science Review, 2023)
This research examines the phenomenon of vote-buying within the Kesu indigenous community during the 2020 North Toraja Regional Head Election. It employs the clientelistic exchange theory proposed by Aspinall and Berenschot (2019). A qualitative research method, utilizing a case study approach, was adopted for this study. Data were collected through a comprehensive review of literature, observations, and documentation from diverse sources, including manuscripts from the Kesu' indigenous peoples, media reports, and previous studies. These data were subsequently subjected to qualitative analysis and presented in a descriptive manner. The primary findings of this research are: (1) The 2020 North Toraja Regional Head Election witnessed a widespread practice of vote-buying, colloquially termed "money politics," particularly within the Kesu indigenous community; (2) Evident clientelistic exchanges were observed, marked by the active participation of the Kesu' indigenous community and traditional stakeholders at grassroots levels, such as Parengge', Anak Patalo, and Patulak, who acted as intermediaries in the vote-buying process.